GENRE SPECIFICITY OF FRENCH CHILDREN’S LITERATURE OF THE 21ST CENTURY - Daniyorova Barchinoy Absattarovna (International Journal of Innovations in Engineering Research and Technology, 2021)
From time immemorial, man has not only struggled for his livelihood, but he has also cared about the longevity of his generation. The world around humanity and its perception of it, the accumulated knowledge,life experience, as well as wise thoughts and conclusions about it are expressed to children in the form of various teachings, in clear means. This is a common feature of the oral literature of all peoples.That is why folklore is the beginning of the national-literary creation of each nation. This feature also plays an important role in children’s literature. Once upon a time in Europe there were collections of fairy tales by the brothers Grimm, H.K. Andersen, S.Perro, J.Rodari, and in time, this phenomenon became the basis for the beginning of French children’s literature. The discovery of the age of self-awareness in the human psyche in childhood has taken place in different nations at different times. Because childhood is a priceless inner world in a person, a period that captivates adults with its innocence and wonders, and the period of adulthood, as the most sincere and childish innocence, begins to be understood as a process of rejuvenation in the spiritual consciousnessof societyquoted